ABO‐incompatible liver transplantation for children under 2 years of age: A case report and a single‐center review. (19th October 2018) - Narumoto, Soichi; Sakamoto, Seisuke; Sasaki, Kengo; Hirata, Yoshihiro; Fukuda, Akinari; Uchiyama, Toru; Irie, Rie; Yoshioka, Takako; Kasahara, Mureo
Abstract: Desensitization with RTX has been broadly introduced in adult LT across the ABO blood type barrier. For pediatric LT, the prophylactic use of RTX has not been standardized, especially for children under 2 years of age. A 20‐month‐old girl with BA underwent living donor LT from her ABO‐I mother. On POD 6, she developed combined T cell‐mediated and AMRs. Steroid bolus injection was immediately introduced, followed by antibody‐depleting therapy with PE and IVIG. Based on a peripheral blood lymphocyte analysis by fluorescence‐activated cell sorting, ATG and RTX were introduced for refractory rejection. Although she recovered from the combined rejections, IHBCs were inevitable as a consequence. We recommend extending the desensitization protocol to cover children under 2 years of age in order to prevent life‐threatening complications.